Elizabeth Taylor : the grit & glamour of an icon - Brower, Kate Andersen (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2022)
Elizabeth Taylor was the last major star to come out of the old Hollywood studio system and she is a legend known for her beauty and her magnetic screen presence in a career that spanned most of the twentieth century and nearly sixty films. But her private life was even more compelling than her Oscar-winning on-screen performances.
Prologue -- Elizabeth the first -- The most beautiful creature: the 1930s, 1940s, and 1950s -- Passion and pain: the 1950s and 1960s -- Lavish love: the 1960s and 1970s -- Survivor: the 1970s and 1980s -- True grit: the 1980s and 1990s -- A legacy of love: the 1990s to 2011 -- Afterword: Lust for life.
"Includes unpublished letters, photographs, and private reflections"-- Cover.
Includes bibliographical references (pages 471-472) and index.
Keywords: Taylor, Elizabeth, -- 1932-2011.; Taylor, Elizabeth, -- 1932-2011 -- Biography; Motion picture actors and actresses -- California -- Los Angeles -- Biography; Motion picture actors and actresses -- Great Britain -- Biography; Biographies